Internationalizing STEM education in Laos: Institutional responses to global higher education - Sisavath, Soubin (American Journal of STEM Education, 2026)
As science, technology, engineering, and mathematics (STEM) education becomes increasingly important for national development and global competitiveness, higher education institutions are under growing pressure to equip graduates with both technical expertise and international competencies. This qualitative study examines how universities in the Lao People’s Democratic Republic (Lao PDR) are responding to the internationalization of STEM education. The research draws on an analysis of institutional policy documents and semi-structured interviews with 29 administrators and academic staff from four public universities. The findings indicate that universities have adopted an “open-door” approach to internationalization through four primary strategies: student and academic mobility, international research collaboration, internationalization at home, and strategic institutional partnerships.